Methodology and the hydroecological state assessment of lake Krymne - Fesyuk, V. O.; Moroz, I. A. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2025)
Purpose. To develop and test a methodology for the indicative and spatial-temporal quantitative assessment of the ecological status of Lake Krymne in order to determine its current ecological stability, identify hydroecological problems, and outline priority directions for its further use and monitoring. Methods. Field hydrological studies, cartographic methods, remote sensing, mathematical modeling and forecasting. Results. The morphometric characteristics of the lake have changed compared to 1933: the area and the volume decreased due to mid-to-late 20th century land reclamation. The lake’s catchment retains features of natural landscapes. However, the lake undergoes significant transformation: part of the riparian zone is plowed, local waste dumps are recorded, and recreational pressure is increasing. Anthropogenic impacts contribute to the inflow of biogenic substances. Water quality deterioration is observed, with increased organic matter, phosphates, and ammonium, periodic oxygen deficits and signs of eutrophication. Remote sensing analysis (synthetic NDVI index) confirms seasonal fluctuations and summer productivity increases, with local growth of algae and macrophytes. The lake is sensitive to pressure and requires continuous monitoring. Main sources of anthropogenic impact are runoff from settlements, agricultural fields, and waste dumps. Conclusions. Lake Krymne has a satisfactory hydroecological status, but a tendency toward deterioration is evident. This process is driven by increased biogen content in the water, eutrophication, and seasonal vegetation development. Priority conservation measures include maintaining protective riparian buffer zones, optimizing land use, modernizing wastewater systems in nearby settlements, eliminating illegal dumps, and establishing a systematic hydroecological monitoring program for the lake.